Treatment of coronary in-stent restenosis: evidence for universal recommendation? - Akın, Ibrahim; Nienaber, Christoph (Journal of thoracic disease, 2015)
Coronary artery disease, clinically evident as stable angina, acute coronary syndrome (ACS) or ischemic cardiomyopathy is the leading cause for mortality in Western population. With widespread use of coronary revascularization the rate of death from myocardial infarction (MI) has decreased, whereas mortality from heart failure is rising. Percutaneous coronary intervention (PCI) initially performed as “plain old balloon angioplasty” (POBA) has established standards over the last 25 years with the introduction of bare-metal stents (BMS), drug-eluting stents (DES), drug-coated balloon (DCB) and scaffolds with concomitant antiplatelet therapy (1,2). However, despite the introduction of these innovations, restenosis remains the Achilles’ heel of any PCI. Traditionally, coronary restenosis is defined as an angiographically detected reduction of ≥50% of vessel diameter at the site of a previously treated segment or its edges. Several surrogate parameters, like late lumen loss (LLL), minimal lumen diameter (MLD), target lesion revascularization (TLR), and target vessel revascularization (TVR) were introduced to better describe the nature of restenosis. With POBA the rate of restenosis, mainly driven by recoil and proliferative remodelling, was up to 30-60% at 6 months (3). BMS eliminated the issue of recoil but induced neointimal hyperplasia, and the term in-stent restenosis in 16-44% of cases (4). Detailed analyses revealed that restenosis after placement of BMS occurred in 42%, 21%, 30%, and in 7% as focal, diffuse, proliferative and total, respectively (5). The introduction of first-generation DES has substantially reduced both angiographic and clinical appearence of restenosis both in randomized clinical trials and in large-scale registries over 4 years (6). Second-generation DES are typically coated with new polymers and drugs resulting in fewer side-branch occlusion, less periprocedural infarction and restenosis rates (7). However, with widespread use of newer generation DES in complex lesions and “off-label” use rates of restenosis are still high at 12% (8). In-stent restenosis has traditionally been considered benign with recurrent symptoms but without any prognostic impact. However, several analyses revealed that 30-60% of patients develop ACS, predominantly with unstable angina and in 5% with ST-elevation myocardial infarction (STEMI) (9). The treatment strategy for restenosis has changed over 25 years and included conventional POBA, cutting or scoring balloon, BMS, vascular brachy-therapy, same DES (“homo-DES”), different DES (“hetero-DES”), drug-eluting balloon (DEB) and even bypass surgery. POBA, with compliant or non-compliant balloons, was one of the first strategies used in patients suffering from restenosis. Despite reasonable outcomes in “focal” restenosis, long-term results of patients with diffuse pattern were less favourable. The use of a cutting balloon preventing slippage, ensured higher luminal gain and led to better clinical outcomes. The use of BMS for BMS restenosis (“sandwich technique”) was supported by the fact of larger acute luminal gain. In RIBS I, comparing balloon angioplasty with BMS implantation for BMS restenosis, patients revealed better acute angiographic results as well as better long-term clinical outcomes in the subset of large vessels (>3 mm) and in the setting of restenosis affecting the stent edge (10). Clinical and angiographic results with DES for BMS restenosis were superior to those with balloon angioplasty, BMS or brachytherapy in several randomized trials (11). Treatment of in-stent restenosis after DES is very challenging and is gaining momentum with the widespread use of DES in primary stenting. Initial experience revealed that the use of DES is associated with better outcomes than other techniques (12). The question whether the same stent or another stent will be supior was addressed in the ISAR-DESIRE 2 trial which not only confirmed that repeat DES implantation is safe for DES restenosis up to 1 year but also showed that using either SES or PES for DES restenosis has similar anti-restenotic efficacy (13). More recently, the concept of DCB for restenosis have been proven to be very effective in patients with both BMS as well as DES in-stent restenosis (14) with the advantage of avoiding multiple stent layers; DCB are noninferior to paclitaxel-DES and both DCB and paclitaxel-DES are superior to POBA (15).